Uveitis following COVID-19 vaccination: A literature review for Canadian ophthalmologists (Canadian Eye Care Today, 2022)
The advent of SARS-CoV-2 (COVID-19) vaccines markedly reduced adverse outcomes associated with COVID-19 infection. With over 12 billion doses of COVID-19 vaccines administered globally as of June 2022, reports have emerged of ocular sequelae following immunization. Vaccination remains the most effective way to reduce the risk of COVID-19-related morbidity and mortality. However, it is important for ophthalmologists to understand the potential adverse events related to SARS-CoV-2 vaccination to provide opportunity for appropriate patient counselling and diagnosis. This review outlines the reported associations between COVID-19 vaccination and uveitis, including proposed mechanisms and recommendations for treating ophthalmologists.